The International and Political Journal: Regional variables and their repercussions on Iraqi-Turkish economic relations - Sobhi, Assistant lecturer Shahd Adel (The International and Political Journal, 2024)
In the midst of the developments that Iraq and Turkey witnessed at the beginning of the twenty-first century in light of the unipolarity represented by American hegemony, and the consequences of economic globalization, Turkey aspires to become a leading economic and political power in the region, with a pivotal role, thanks to the capabilities it possesses. Economic, industrial and technical, and their natural and geographical characteristics and conditions. At a time when the Turkish economy, which continued to face many economic crises over the past century, was able to, However, he was able, through economic reform policies and choosing appropriate strategic approaches, to overcome his conditions at that time, and began moving towards economic advancement, until the Turkish economy became one of the largest (20) economies in the world, by achieving reliable growth rates and increasing the competitive capabilities of Turkish goods in the markets. Globally, and its average per capita income is high compared to neighboring countries.